Republished: Rapid delayed growth of ruptured supraclinoid blister aneurysm after successful flow diverting stent treatment. (28th July 2016) - Lang, Stefan Thomas; Assis, Zarina; Wong, John H; Morrish, William; Mitha, Alim P
Abstract : A 62-year-old woman presented with a subarachnoid hemorrhage secondary to a ruptured right supraclinoid internal carotid artery blister aneurysm. She was treated in an emergent fashion with two flow diverting pipeline embolization devices (PED) deployed in a telescoping fashion. CT angiography performed for unrelated reasons at 7 months showed successful treatment of the aneurysm without evidence of residual aneurysm. However, a follow-up digital subtraction angiogram performed at 9 months showed a large aneurysm in a modified position compared with the original aneurysm. This is the first case of rapid regrowth of a supraclinoid blister aneurysm after successful treatment with a PED, and demonstrates the need for close follow-up for similar aneurysms treated with this novel device.